A Case Series of Critical Methanol Poisoning - Namthaisong, Kriengkrai; Tangrungruengkit, Mintra; Danutra, Rujaya; Chongchitpaisan, Wanna (Journal of The Department of Medical Services, 2025)
Methanol poisoning commonly causes severe neurological and visual symptoms can be fatal. This study aimed to describe the assessment of severe neurological and visual symptoms in patients with methanol poisoning resulting from the ingestion of traditional herbal liquor. A total of 25 patients who consumed herbal liquor and presented to the emergency department were studied. Among them, 7 patients exhibited severe neurological symptoms and visual disturbances. Most of the affected individuals were male and of working age. Abnormal findings were observed in 5 patients from brain computed tomography (CT) scans, all showing bilateral putamina necrosis. In addition, diffuse cerebral edema and bilateral occipital necrosis were also noted. Visual and ophthalmic evaluations revealed abnormalities in 3 patients. Retinal abnormalities were detected, with some improvement upon follow-up. However, reduced visual acuity was found in others, and optical coherence tomography (OCT) showed retinal nerve fiber layer (RNFL) thinning by 50-70%. Methanol poisoning from traditional herbal liquor, especially when patients present late to the hospital, can result in severe neurological symptoms and death. For survivors with permanent impairments, a referral for a return-to-work evaluation and work modification, based on their health status, is recommended.